SIMULASI KENDALI PROPORTIONAL INTEGRAL DERIVATIVE DAN LOGIKA FUZZY PADA SISTEM EKSITASI AUTOMATIC VOLTAGE REGULATOR DENGAN SIMULINK MATLAB - Jati, Pamungkas; Sunarno, Sunarno; Sujarwata, Sujarwata (Universitas Negeri Semarang, 2017)
AVR (Automatic Voltage Regulator) is the primary device for a generator stability, therefore performance of an AVR must be considered. Implementation of controller can be used to improve performance of an AVR. Now the controller is widely applied in industry, namely PID and fuzzy. Modelling carried out to determine the performance of AVR. The modelling of AVR system and its controller are built using Matlab Simulink. PID controller is designed by tuning method of Ziegler-Nichols (ZN) and Tyreus-Luyben (TL) while fuzzy controller is built by two input variables and one output variable, each consists of 7 MF so can be obtained 49 fuzzy rules. Based on transient response analysis, PID controller with TL method is better than ZN method and overall the comparison results of controller demonstrated that the PID controller provides a better performance in three parameters (rise time, peak time, and settling time), while the fuzzy controller provides a better performance in overshoot parameter.